The Effect of Activity on Firm Value with Dividend Policy as an Intervening Variable - Ijma; Syahputra , Rendy Aziz; Wahdania (Fakultas Ekonomi, Universitas Negeri Jakarta, Indonesia, 2024)
This research aims to determine and explain whether dividend policy mediates the effect of activity on company value. The population in this study were 19 Processed food sub-industry companies listed on the Indonesia Stock Exchange for the 2018-2022 period. The data analysis tools used were the classical assumption test, path analysis, and hypothesis testing consisting of the coefficient of determination test, t-test, and Sobel test with the help of the SPSS Version 29 application. The research results showed that: (1) Activity does not affect dividend policy. (2) Activity has a significant effect on firm value. (3) Dividend policy does not affect firm value. The results of the Sobel test showed that (4) dividend policy could not mediate the effect of activity on company value. This is because investors focus more on the company's ability to generate profits and grow in the future, and high dividends can give a negative signal. Companies that retain profits and reinvest in profitable projects are generally preferred by investors and have the potential to increase the company's value in the future.